Self-compliance and high-performance GeTe-based CBRAM with Cu electrode. (January 2023) - Zhao, Jiayi; Chen, Qin; Zhao, Xiaohu; Yang, Gaoqi; Ma, Guokun; Wang, Hao
Abstract: Conductive bridging random access memory (CBRAM) has been considered as a promising candidate for next-generation non-volatile memory. However, there are always problems of high-power consumption in CBRAM. In this study, a GeTe-based resistive random access memory (RRAM) with an active Cu electrode is fabricated, which reveals significant behavior of low forming voltage (<|-2|V). At the same time, the device exhibits the property of self-compliance, which is essential for protection of the device and reduction of the leakage current. Furthermore, the resistance switching (RS) mechanism of the device is proved to be filament-type, which helps explain the self-compliance phenomenon in detail. These properties provide an effective solution to the achievement of low-power consumption in CBRAM, and show a potential for the scalability of the device and high-density integration in the cross-bar array.